Highly Skin-Conformal Laser-Induced Graphene-Based Human Motion Monitoring Sensor - Jeong, Sung-Yeob (Nanomaterials (Basel), 2021)
Bio-compatible strain sensors based on elastomeric conductive polymer composites play pivotal roles in human monitoring devices. However, fabricating highly sensitive and skin-like (flexible and stretchable) strain sensors with broad working range is still an enormous challenge. Herein, we report on a novel fabrication technology for building elastomeric conductive skin-like composite by mixing polymer solutions. Our e-skin substrates were fabricated according to the weight of polydimethylsiloxane (PDMS) and photosensitive polyimide (PSPI) solutions, which could control substrate color. An e-skin and 3-D flexible strain sensor was developed with the formation of laser induced graphene (LIG) on the skin-like substrates. For a one-step process, Laser direct writing (LDW) was employed to construct superior durable LIG/PDMS/PSPI composites with a closed-pore porous structure. Graphene sheets of LIG coated on the closed-porous structure constitute a deformable conductive path. The LIG integrated with the closed-porous structure intensifies the deformation of the conductive network when tensile strain is applied, which enhances the sensitivity. Our sensor can efficiently monitor not only energetic human motions but also subtle oscillation and physiological signals for intelligent sound sensing. The skin-like strain sensor showed a perfect combination of ultrawide sensing range (120% strain), large sensitivity (gauge factor of ~380), short response time (90 ms) and recovery time (140 ms), as well as superior stability. Our sensor has great potential for innovative applications in wearable health-monitoring devices, robot tactile systems, and human–machine interface systems.